Electrostatic interaction of tumor-targeting adenoviruses with aminoclay acquires enhanced infectivity to tumor cells inside the bladder and has better cytotoxic activity - Soo-Yeon Kim; Whi-An Kwon; Seung-Pil Shin; Ho Kyung Seo; Soo-Jeong Lim; Yuh-Seog Jung; Hyo-Kyung Han; Kyung-Chae Jeong; Sang-Jin Lee (Taylor & Francis Group, 2018)
In a previous report, 3-aminopropyl functionalized magnesium phyllosilicate (aminoclay) improved adenovirus transduction efficiency by shielding the negative surface charges of adenovirus particles. The present study analyzed the physicochemical characterization of the electrostatic complex of adenoviruses with aminoclay and explored whether it could be utilized for enhancing tumor suppressive activity in the bladder. As a result of aminoclay-adenovirus nanobiohybridization, its transduction was enhanced in a dose-dependent manner, increasing transgene expression in bladder cancer cells and in in vivo animal models. Physicochemical studies demonstrated that positively charged aminoclay led to the neutralization of negative surface charges of adenoviruses, protection of adenoviruses from neutralizing antibodies and lowered transepithelial electrical resistance (TEER). As expected from the physicochemical properties, the aminoclay enabled tumor-targeting adenoviruses to be more potent in killing bladder cancer cells and suppressing tumor growth in orthotopic bladder tumors, suggesting that aminoclay would be an efficient, versatile and biocompatible delivery carrier for intravesical instillation of adenoviruses.